Evolution of the Physical Phenotype of Fetal Alcohol Spectrum Disorders from Childhood through Adolescence. (9th February 2021) - Jacobson, Sandra W.; Hoyme, H. Eugene; Carter, R. Colin; Dodge, Neil C.; Molteno, Christopher D.; Meintjes, Ernesta M.; Jacobson, Joseph L.
Abstract : Background: This paper reports findings from the first longitudinal study on the evolution of the physical phenotypes of fetal alcohol syndrome (FAS) and partial FAS (PFAS) from early childhood through adolescence. Methods: The sample consisted of 155 children (78 males and 77 females) born to women recruited at an antenatal clinic serving a Cape Coloured (mixed ancestry) population in Cape Town, South Africa. Two expert FASD dysmorphologists, blind regarding prenatal alcohol exposure, independently evaluated each child's growth and dysmorphology at 4 clinics conducted over an 11‐year period. Case conferences were held to reach consensus regarding which children had FAS or PFAS growth and physical features using the Revised Institute of Medicine (2005) guidelines. Results: The prevalence of the physical phenotype was stable across the 4 ages for about half of the children with FAS and about one‐third of those with PFAS but more variable for the others. Test–retest reliability was substantial for the FAS phenotype, but poorer for PFAS. Two distinct patterns were seen: a "strong phenotype" that was consistently identified and a less consistent one in which dysmorphic features and/or anthropometric deficits fluctuated or diminished with age. The physical phenotype was most apparent during early childhood and least apparent during puberty, due to differences in timing of the growth spurt and the evolving adult face. Short palpebral features and small head circumference diminished with age, flat philtrum fluctuated, while thin vermilion and weight and height restriction were stable. Conclusions: Key facial features that characterize FASD in early childhood diminish or evolve in some individuals, making diagnostic examinations that rely on these characteristics most sensitive during early childhood and school age. Moreover, puberty poses classification problems due to variability in timing of the growth spurt. Given that several features and small head circumference diminished with age, many individuals would be misdiagnosed if only examined at a later age. Abstract : Expert FASD dysmorphologists examined 155 children born to heavy drinking and control women at four clinics conducted over an 11‐year period. The FAS physical phenotype was most apparent during childhood and least during puberty. Short palpebral features and small head circumference diminished with age, flat philtrum fluctuated, while thin vermilion and weight and height restriction were stable. Given that several features and small head circumference diminished, many individuals would be misdiagnosed if only examined at a later age.